Plant-based dietary miRNAS: cross-border regulatory factors for regulating glycolipid metabolism and their nutritional intervention strategies - Liu, Yaping; Tao, Xingyue; Wang, Xiaoxiao; Lv, Huilin; Luo, Huomin; Li, Peifeng (Frontiers in Nutrition, 2025)
Disorders of glucose and lipid metabolism represent a major global health burden, driving the need for innovative nutritional interventions. Emerging evidence suggests that dietary microRNAs (miRNAs) from plants can act as cross-kingdom regulators. These molecules may survive digestion, enter the mammalian circulation, and modulate host gene expression to influence glycolipid homeostasis. This review comprehensively synthesizes current knowledge in this field, beginning with the dietary origins of plant miRNAs and evaluating their stability during food processing and gastrointestinal passage. We critically examine the mechanisms and ongoing debates regarding their absorption, transport, and biodistribution. The review further elucidates how specific plant miRNAs target key genes and signaling pathways involved in glucose and lipid metabolism, while also exploring their interplay with gut microbiota and metabolic inflammation. We summarize supporting evidence from in vitro and animal models, acknowledge translational challenges in human applications, and discuss persistent controversies regarding their bioavailability and biological relevance. Looking forward, we explore potential strategies to harness these molecules for nutrition therapy, including dietary source optimization, advanced processing techniques, engineered delivery systems, and precision nutrition approaches based on individual metabolic and miRNA profiles. Finally, we identify major knowledge gaps and future research priorities, such as clarifying uptake mechanisms, validating efficacy in well-controlled human trials, and establishing safety and regulatory frameworks. This review provides a foundational understanding and forward-looking perspective on plant-derived dietary miRNAs as novel factors in nutrition and metabolic disease management.